2020
DOI: 10.1634/theoncologist.2020-0406
|View full text |Cite
|
Sign up to set email alerts
|

Professional Medical Writer Assistance in Oncology Clinical Trials

Abstract: Background The use of professional medical writers (PMWs) has been historically low, but contemporary data regarding PMW usage are scarce. In this study, we sought to quantify PMW use in oncologic phase III randomized controlled trials (RCTs). Methods We performed a database query through http://ClinicalTrials.gov to identify cancer‐specific phase III RCTs; we then identified whether a PMW was involved in writing the associated trial manuscript reporting primary endpoint results. Results Two‐hundred sixty tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is important to note that this study does not suggest that there are inherent differences between the research of for‐profit and nonprofit funding sources, and for‐profit sources are important vehicles for innovation. The above findings do, however, raise questions about the influence of funding sources in oncology research and how anticipated revenue streams may impact the types of trials conducted as well as their design, accrual, reporting, and outcomes 14–20 ,. 33‐40 In recent years, the majority of phase 3 trials have been funded by industry 14,41,42 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…It is important to note that this study does not suggest that there are inherent differences between the research of for‐profit and nonprofit funding sources, and for‐profit sources are important vehicles for innovation. The above findings do, however, raise questions about the influence of funding sources in oncology research and how anticipated revenue streams may impact the types of trials conducted as well as their design, accrual, reporting, and outcomes 14–20 ,. 33‐40 In recent years, the majority of phase 3 trials have been funded by industry 14,41,42 .…”
Section: Discussionmentioning
confidence: 93%
“…The above findings do, however, raise questions about the influence of funding sources in oncology research and how anticipated revenue streams may impact the types of trials conducted as well as their design, accrual, reporting, and outcomes. [14][15][16][17][18][19][20][33][34][35][36][37][38][39][40] In recent years, the majority of phase 3 trials have been funded by industry. 14,41,42 It is worth noting that the process for approving new pharmaceuticals in the United States is different from the process of approving new surgical equipment or adopting new radiotherapy techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, more than one-third of RCTs in the present study cohort involved a medical writer, a trend that has skyrocketed in recent years, with 67% of RCTs published in 2020 from the cohort using medical writers (Figure 3). This is consistent with recent work by Kouzy et al, who reported that 43% of oncology RCTs used professional medical writers. There is reason to be concerned that medical writers may unduly influence the interpretation of trials.…”
Section: Discussionmentioning
confidence: 99%